PENGARUH METODE EKSPERIMEN TERHADAP KONSENTRASI ANAK BERKEBUTUHAN KHUSUS DALAM PEMBELAJARAN SAINS - Khamidun, Diana; Khoiroh, Elif Mauzidatuf (JIV-Jurnal Ilmiah Visi, 2013)
The research objective is to provide accurate information and picture about the influence of the experimental method to the concentration of children with disabilities in beginning science activities. The research was carried out in the Training Park and Observation of Foreign School in Semarang, with a total sample 14 early age children with special needs. This study used an experimental design providing a group with treatment to see the influence. T-test was used to prove the hypothesis that the experimental method can have a significant influence on the concentration of children with disabilities to learn beginning science. Experimental method as a learning method in preschool classes in the institution of early childhood development, can influence the children’s ability/concentration in learning. This method gives children the opportunity to know and interact with the environment and enable them to focus and concentrate on learning activities in the classroom.